Avaliação do Estoque de Caranguejo-uça, Ucides cordatus (LINNAEUS, 1763) na Zona Estuarina do Rio Pacoti, Estado do Ceará - Marques, Douglas Ferreira Marques (2008)
The mangrove crab Ucides cordatus is the main fishing resource explored in North and Northeast mangrove areas in Brazil. The mangrove crab capture provide the main income form many families living along the estuaries in these areas. The U. cordatus populations have suffered intense predatory capture, coupled with high mortality rates during transport and distribution. The demand for crabs in the city of Fortaleza are steadily increasing in the last three decades, and natural populations of crabs in Ceará state’s mangroves have diminished considerably, forcing the importation of crabs from other producing centers, such as Piauí and Maranhão. This work presents information on the population structure and reproductive dynamics of U. cordatus population from the Pacoti river estuary, in the metropolitan region of Fortaleza, Ceará. Data was gathered monthly from May 2006 until July 2007, through random sampling the mangrove area. The size structure analysis showed that the largest portion of individuals were in the 35,4 --| 38,4mm and 42,1 --| 45,0mm class intervals of carapace length (CC). Males were significantly larger than females regarding carapace length and width. The CC/LC ratio of males and females, on the other hand, were not different. The determination coefficients of allometric growth (b) were tested and showed a negative allometric growth for both sexes (b<1). The reproductive period started in December and ended in May, with highest intensity in January. The smallest ovigerous females measured 30,3 mm in carapace length. The molt period began in June, ending in December with a maximum and minimum in July and September respectively, for the males, and two maximum peaks and a minimum in October, December and July, respectively, for the females. The analyses of the sex ratio by trimester showed predominance of males in the 4th trimester of 2006, whereas the females were more numerous in the 1st trimester of 2007. The mean density of mangrove crab was estimated in 2,2 crabs/m2